Soybean Inventory Management at Gesit Tahu Factory Using the Economic Order Quantity (EOQ) Method - Hidayat, Rahmat; Wahyuda, Wahyuda; Sitania, Farida Djumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Gesit Tahu is a small-scale factory engaged in the tofu industry, in the production process is closely related to the supply of the main raw material, namely soybeans. Gesit Tahu has not been optimal in controlling the level of raw material inventory where this factory has experienced a shortage of soybean inventory due to high demand, so it requires a method that can optimize raw material purchases and minimize inventory costs, the right method in solving this problem is using the Economic Order Quantity (EOQ) method. The purpose of this study is to determine the inventory control of Gesit Tahu soybean raw materials by comparing the current inventory management policy at the factory and using the EOQ method. The results of this study that inventory control is more efficient using the EOQ method, it is proven that it can make savings from the cost factor that must be incurred, it can be seen that if the Gesit Tahu factory applies the EOQ method, namely IDR 2,223,077,461, it is a minimum compared to the factory policy method within one year, which is IDR 2,223,619,662. The optimal order quantity for soybean needs is 72.87 sacks (73 sacks) for one order. The frequency of ordering soybean needs is 43.49 or 44 times/year. The calculation of safety stock to anticipate unexpected shortages is 1.64 sacks or 2 sacks. The calculation of the reorder point obtained to determine the point at which the order is placed again so that the ordered goods arrive on time before the inventory runs out is 21.93 sacks or 22 sacks.